MOTIVASI DALAM PEMBELAJARAN BAHASA ARAB SEBAGAI BAHASA ASING - Ulil Albab (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2019)
Introduction. The existence of demotivating phenomena in the process of learning Arabic is very much felt by the instructor at this time, it can be seen from the low of the final result of students. Data Collection Method. Using a study literature approach Analysis Data. Using a descriptive analysis Results and Discussions. There is a positive correlation to the role of motivation in language learning. This is evidenced by several studies that say that motivation can improve the results of student learning achievement. In the research conducted by Nik Mohd Rahimi Nik Yusoff, Zamri Mahamod, Kamarulzaman AB. Ghani, found that the relationship between motivation towards proficiency in hearing Arabic and achieving proficiency in hearing Arabic (r = 0.613). This shows that the achievement of students in the ability to hear Arabic is somewhat influenced by students' motivation towards the ability to hear Arabic. Keyword : learning motivation, arabic language, foreign language